Advances in clinical basic research: Performance, treatments, and mechanisms of Parkinson disease. Issue 4 (23rd December 2021) - Yang, Ting‐Ting; Liu, Yu‐Cong; Li, Jing; Xu, Hui‐Chan; Li, Shun‐Lian; Xiong, Liu‐Lin; Wang, Ting‐Hua
Abstract: The loss of neuronal in the substantia nigra of the elderly contributes to striatal damage and plays a critical part in the common forms of neurodegenerative diseases such as Parkinson disease (PD). The deficit of dopamine is one of the most familiar neuropathological features of PD as well as α‐Synuclein aggregation. The peripheral autonomic nervous system is also affected negatively during the course of the disease, although the subsistent of dyskinesias and else major motor characteristic deficits take significant role in the diagnostic methods during clinical practice, which is related to a number of non‐motor symptoms that might increase aggregate risks. Multiple pathways and mechanisms are involved in the molecular pathogenesis: α‐Synuclein, neuronal homeostasis, mitochondrial function, oxidative stress, as well as neuroinflammation. Investigations in the last few years for diagnostic biomarkers used neuroimaging, including single photon emission computed tomography as well as cutting‐edge magnetic resonance imaging techniques, which has been presented to facilitate discrepant diagnosis. Pharmacological treatment is also important and efficient in equal measure. In addition to reliance on striatal dopamine replacement therapy, many solutions that are used for motor or nonmotor symptoms in these patients are available. Abstract : Nonmotor symptoms can occur to varying degrees throughout the course of Parkinson disease (PD), with a prodrome that can occur for years or even decades before the onset of motor symptoms (early‐stage PD) and is characterized by the appearance of specific nonmotor symptoms (promotor PD).